Just write : creating unforgettable fiction and a rewarding writing life - Bell, James Scott (Writer's Digest Books, 2016)
"Half intensive craft workshop and half practical advice on building and sustaining a successful writing practice, Just Write marries craft and technique with encouragement and insider advice. Featuring the best posts written for the Kill Zone blog (a thriller writers' blog that has appeared on WD's 101 Best Websites for Writers multiple times) as well as brand-new material, the book will serve as a guide for all fiction writers on mastering the craft and "keeping at it," no matter what their chosen genre."--provided by Amazon.com.